Peru, an unfinished imaginary; a reflection from the work of Matos Mar about the current situation - Ramirez Cornelio, Flavio Marino (2021)
The current political crisis in Peru leads us to ask in some way how the problems we are going through arose. If we are talking about a temporary problem typical of the presidential elections or if we are really talking about a structural problem that concerns us as a society and whose latent symptoms appear every five years. Matos Mar will explain to us how migrations mark a before and after on the imaginary that we build about Peru, or if there are many. This is an anthropological and sociological work that will try to explain us about the origin of the neighborhoods on the margins of current Lima and how this reconfigured the socio-political scenario of Peru and in turn as the state in its inability to resolve social economic demands From this new social reconfiguration originates a new social and economic phenomenon that we suffer to this day, informality.